Programming The Web Using XML / Ellen Pearlman, Eileen Mullin. - Pearlman, Ellen; Mullin, Eileen (New York : McGraw Hill, 2004)
Compares HTML, XHTML, and XML, and includes examples of how XML is being used to help readers appreciate the power of XML. This text also provides a coverage of the rules and standards for XML, which is very critical in programming XML. It is designed to help those who have a background in HTML make the transition to XML.
Keywords: Internet Programming; World Wide Web; XML (Document markup language)